Penderitaan Tokoh Perempuan dalam Novel Romansa 2 Benua Karya Pipiet Senja - Mahfira, Hannifia Dalia Azza; Fauzan, Akhmad (Suara Bahasa, 2024)
This research is motivated by the prevalence of violence against women, which is a significant factor contributing to their suffering. The purpose of this study is to describe the various forms of suffering experienced by female characters in the novel "Romansa 2 Benua" by Pipiet Senja. The author uses a descriptive qualitative method with a feminist literary criticism approach. The primary data source is the novel "Romansa 2 Benua" by Pipiet Senja, which consists of 223 pages, and the data includes dialogues, paragraphs, or sentences that depict the suffering of female characters. This novel was chosen because it contains a female character who experiences a lot of suffering due to the actions of men, so it can be used as an object of research. Data collection techniques involve reading and note-taking, followed by analysis through identifying the forms of suffering experienced by female characters, categorizing them, and drawing conclusions or verifying the obtained data. The study reveals that the suffering experienced by female characters in the novel "Romansa 2 Benua" includes physical suffering, psychological suffering, and sexual suffering.